STUDENT PERCEPTION OF ONLINE LEARNING DURING COVID: FINDINGS FROM A INDIAN UNIVERSITY - Agarwal, Vinti; Khara, Sibaram (International Journal of Engineering Technologies and Management Research, 2021)
The pandemic threw student lives in disarray as they were forced to transition overnight to an online system of education for which they and the faculty were least prepared. In addition to the uncertainty relating to academic schedules, mode of examinations and evaluation patterns, students were forced to adapt to learning online without the facility of books, laboratories, libraries, computer systems and interactive classrooms. What was the perception of students regarding online learning as a result of this quick transition has been explored through a case of private university in Delhi-NCR region with an enrolment of 12000 students. The students were administered a survey with questions on the economic impact of the pandemic, ownership of digital devices, access to internet, and perception of online education. The 2463 student responses received indicated that perception of online learning was quite low even at the level of higher education despite the access to smartphones and internet. The factors scores relating to perception of quality of online education however were found to significantly vary across age, ownership of device and economic impact of covid.